Political Art After the Communicative Turn - Fisher, Tony (Escritura e Imagen, 2020)
Writing in response to Sartre’s essay on engaged literature, Adorno proclaimed: “This is not the time for political works of art; rather politics has migrated into the autonomous work of art, and it has penetrated most deeply into works that present themselves as politically dead”. Today, the theorists of the “social turn” in art have all but rejected Adorno entirely, embracing instead a new kind of commitment in art. In this essay, I revisit this longstanding dispute about the social “efficacy” of art in both its classical and contemporary forms. In asking how we are to understand a political work of art today, I examine two theories of effect, based on an analysis of Habermas’s “communicative turn” –one that I allege leads to a sociological reduction of the political in art; and the other that I suggest provides a basis for understanding art’s political efficacy grasped in terms of what I call a “perlocutionary” or “aleatory” theory of political effect.